HEAVY METALS CONTAMINATION OF SHALLOW GROUND WATER IN DIRECT CONTACT WITH FAILED SEPTIC TANKS - KOCHARY, SHAWKAT AHMED YASEEN; NOORI, BAHZAD MOHAMMAD ALI; BYL, TOM D. (Journal of Duhok University, 2017)
Improper use of septic systems has shown to contribute in ground water contamination by heavy metals, toxic chemicals, and organic chemicals typically found in septic tank cleaning products. Therefore, it suggested evaluating the implication of heavy metals on shallow ground water contamination with direct contact of failed septic tanks. In conducting this research, a laboratory physical vadose model with a vertical flow direction was designed and packed with Silt-Clay soil, which was modified by replacing (20% by weight) of fine sand to satisfy the desired hydraulic conductivity to collect water samples, using a new packing technique other than the ordinary compaction procedure. The model was then fully saturated, well-drained, and run using raw filtered septic water. The model was run for three months and water samples were collected on daily basis at 12.5cms from top of model representing 6.25m underground (model scale was 1:50). Collected samples were analyzed weekly for any pollution occurrence in ground water quality with reference to heavy metals including Fe, Pb, Cu, Cd, Zn, Cr, Al, and Mn. Analytical results used to identify trends of contamination and predict future trends. Results revealed that Fe and Mn were much higher than the permissible limits of world health organization (WHO, 2008) then Al and Cd. Cr fluctuated around the permissible level, Zn precipitated and disappeared within the soil while both of Pb and Cu were safe and at very low level. This study helps the local government in establishing precaution strategies for ground water management to protect public health.